PENYULUHAN KESEHATAN KECACINGAN DAN PEMERIKSAAN KADAR HEMOGLOBIN PADA ANAK SEKOLAH DASAR DI KECAMATAN UBUD-GIANYAR - suyasa, ida bagus oka; Dharmawati, I Gst Agung Ayu; Bekti, Heri Setiyo (Jurnal Pengabmas Masyarakat Sehat, 2025)
The prevalence of Soil Transmitted Helminths (STH) in Bali in 2004 reached 58.3% -96.8% in elementary school children. The priority problem to be corrected in this community service is the lack of knowledge of elementary school children regarding worms. This method of community service provides counseling, checking hemoglobin levels, checking for worm eggs in participants' feces and strengthening small doctors from SDN 1 Ubud. In the extension activities, there was an increase in participants' insight and knowledge, as seen from the increase in the number of participants who managed to get good grades, from 9.9% (pretest) to 97.5% (posttest). When checking hemoglobin levels, the majority of community service participants, 89.6% (69 people) had normal levels (9-14 gr/dl). Meanwhile, to check for the presence of worm eggs, the majority (72 people) of the community service participants did not find worm eggs (94.7%). One of the results of strengthening Little Doctors at SDN 1 Ubud is the birth of a work program (proker) to socialize worm prevention.